Veno-venous extracorporeal membrane oxygenation in a patient with severe acute respiratory failure – case report - Kubisa, Bartosz (Kardiochir Torakochirurgia Pol, 2015)
Acute respiratory failure resistant to conventional pulmonary therapy often requires intensive medical care. In rare cases, ventilator therapy proves insufficient, and only the option of employing veno-venous extracorporeal membrane oxygenation (ECMO V-V) remains. The present article describes the case of a 23-year-old patient who experienced severe acute respiratory distress syndrome with associated multiple organ failure. The patient was admitted to the pulmonary ward of the Alfred Sokołowski Regional Pulmonary Hospital in Szczecin-Zdunowo with suspected pneumonia of unknown etiology. After the initial 5 days of diagnostics at the pulmonary ward, the patient required a further 97 days of hospital treatment and spent 63 days at the Intensive Care Unit. There, he underwent ECMO V-V therapy lasting 22 days, which resulted in the improvement of his arterial blood gas parameters and clinical condition.